Reconstruction of article 4 of the law on corruption and the implementation of restorative justice oriented towards the return of state financial losses - Ndururu, Paternus (Institute Of computer Science (IOCS), 2025)
Corruption remains a pervasive issue, affecting all levels of society, from power holders to both the public and commercial sectors. This study investigates the implications of Article 4 of the Corruption Law regarding corrupt perpetrators and its effectiveness in restoring state financial losses. Employing a normative juridical research method, the study underscores the importance of Article 4 in law enforcement against corruption, particularly in financial recovery efforts. This article serves as a crucial balance between penalizing corrupt practices and ensuring accountability, emphasizing that corruption is a grave crime that requires more than just monetary restitution. The findings suggest that the eradication of corruption in Indonesia, as outlined in Law No. 31 of 1999, aims to restore national finances and the economy, highlighting the recovery of state financial losses as a fundamental objective. Specifically, Articles 4 and 18(1)(b) provide a framework for this recovery approach. The study recommends that the government and the House of Representatives prioritize revisions to the Corruption Crime Law to enhance the focus on state financial recovery, thereby strengthening the fight against corruption in the country.